A review on taste masked multiparticulate dosage forms for paediatric for tenacity and toughness improvement - AL-japairai, Khater Ahmed Saeed; Hamed Almurisi, Samah; Almonem Doolaanea, Abd; Syed, Mahmood; Alheibshy, Fawaz; Alobaida, Ahmed; Nadiya, Abdul-Halim; Chatterjee, Bappaditya (Elsevier B.V., 2023)
Taste refers to those sensations perceived through taste buds on the tongue and oral cavity. The unpleasant taste of drugs leads to the refusal of taking the medicine in the paediatric population. It is widely known that a pharmaceutical product's general acceptability is the result of numerous contributing components such as swallowability, palatability (taste, flavour, texture, and mouthfeel), appearance, ease of administration, and patient characteristics. Multiparticulate as a dosage form is a platform technology for overcoming paediatrics' incapacity to swallow monolithic dosage forms, masking many medications' inherent nasty taste, and overcoming the obstacles of manufacturing a commercially taste masked dosage form. This review will discuss the considerations that must be taken into account to prepare taste masked multiparticulate dosage forms in the best way for paediatric use.